Nutrition Knowledge Improves Capabilities Educational Information Communication Service (EIC) Practice Community Pharmacist Health Supplement - Rizki Siti Nurfitria; Tiara Ismadewi Hastuty; Ni Nyoman Sri Mas Hartini (Universitas Muhammadiyah Sumatera Utara, 2023)
Abstract: Community pharmacists as the spearhead of pharmacy services may be asked to provide advice on the use of health supplements through Information Communication and Education services (EIC) such as counselling and drug information. Knowledge of nutrition and health supplements is very important to prevent misuse in consuming these products. The purpose of the study was to determine the extent of the relationship between nutritional knowledge and community pharmacist practice in EIC health supplements. The method used is observational analytic with a cross-sectional approach in Purwakarta Regency in March – April 2022. Data was taken using questionnaires on 59 community pharmacists and then processed qualitatively and quantitatively through the Spearman Rank correlation test using SPSS version 25.0. The results showed that all community pharmacists routinely conduct EIC (100%), most have positions as the first pharmacist practice license (SIPA) (88.6%) and practice in pharmacies (50%). The level of knowledge of nutritional counselling and community pharmacist practice in EIC health supplements falls into the good category (85.8% and 81.32%). The level of knowledge of nutritional counselling and community pharmacist practice in EIC health supplements falls into the good category (85.8% and 81.32%). There was a significant positive relationship between nutritional knowledge and community pharmacist practice in the EIC of health supplements at a significance value of 0.000 (p0.05) and a correlation coefficient value of 0.769 indicating that the relationship is strong.